Factors associated with gonadotropin release and ovulation after exogenous administration of GnRH in Bos Taurus (Veterinary Science, 2022)
The gonadotropin-releasing hormone (GnRH) is a decapeptide, synthesized by the GnRH neurons in the hypothalamus, which stimulates the synthesis and secretion of gonadotrophins (follicle-stimulating hormone, FSH and luteinizing hormone, LH) from the anterior pituitary or adenohypophysis. GnRH agonists with a structure identical or similar to nature have been commercially available since the 1970’s and were initially used for the treatment of follicular cysts and the improvement of fertility in cattle (1). The ovulation of ovarian follicles after GnRH administration was first reported by Schams et al. (2) and Britt et al. (3), but it was not until the 1990’s that GnRH began to be used to control follicular dynamics during the bovine estrous cycle. Studies have shown that a new follicular wave emerges within 2 days after ovulation of the dominant follicle present at the time of GnRH treatment (4,5). This finding facilitated the development of synchronization protocols based on GnRH in combination with prostaglandins (PGF) that allow fixed-time artificial insemination (FTAI), without the  need for heat detection. These GnRH-based protocols are part of the reproductive management, especially in dairy cattle, in many commercial herds around the world. There are several GnRH and PGF-based protocols available for estrus and ovulation synchronization in cattle, most of these protocols have been explained and discussed in detail in other publications (6,7). The objective of this review is to describe the factors associated with the release of LH and ovulatory response after the administration of GnRH, to present relevant information on the effect of steroid hormones on the response to GnRH and, finally, to briefly postulate strategies that could improve the efficacy of GnRH and PGF-based protocols
Keywords: Estrogen; Progesterone; LH release; Follicular dynamics; Artificial insemination